AN ERROR ANALYSIS OF PREPOSITION IN WRITING DESCRIPTIVE TEXT AT THE SEVENTH GRADE STUDENTS OF SMP N 1 NGARGOYOSO KARANGANYAR IN 2021/2022 ACADEMIC YEAR - Yuliana Yuliana; Ch. Evy Tri W (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
The objective of the research were: 1)to find out the type of errors in using preposition of place in writing descriptive text by the students of class VII A in SMP N 1 Ngargoyoso Karanganyar in 2021/2022 academic year, 2) to find out the dominant errors in using preposition of place in writing descriptive text by the students of class VII A in SMP N 1 Ngargoyoso Karanganyar in 2021/2022 academic year, and 3) to find out the causes of errors in using preposition of place in writing descriptive text by the students of class VII A in SMP N 1 Ngargoyoso Karanganyar in 2021/2022 academic year. The method of the research was descriptive qualitative research. This research was conducted on 12 January to 20 January 2022. The subjects of the research were class VII A of SMP N 1 Ngargoyoso, in the class consist 32 students. In technique of collecting the data, the researcher used interview, test, and documentation. To analyze, the researcher used the model of qualitative analysis from Miles and Huberman. This research was Error Analysis. Then, to analyze the data, the researcher used the Corder’s theory. The five texts gave to the students. Then, the type of errors was made by the students was misformation type. In this research, the dominant error in the use of preposition was misformation. In the first text, the dominant preposition was “in” with percentage of 63.7%. In the second text was preposition “at” with percentage of 55.6%. In the third text was preposition “at” with percentage of 60%. In the fourth text was preposition “in” with percentage of 61.7%. In the last text was preposition “in” with the percentage of 59.9%. Then, the causes of error in the used of preposition there were two causes. There were carelessness and first language. It could be conclude, the misformation was the main type of error in the class. The dominants error in the used of preposition was misformation with percentage of 100% each text. The causes of error in the used of preposition were carelessness and first language. Keywords: Error Analysis, Preposition, Descriptive Text